49.0k views
0 votes
12x - y = -4
4x - 3y = -6 (1 point)

User Gaganbm
by
4.3k points

2 Answers

3 votes
First step Substitute the value of y
4x-3(4+12x)= - 6
And this is your final answer
12x - y = -4 4x - 3y = -6 (1 point)-example-1
User StXh
by
5.5k points
3 votes

Answer:

Explanation:

12x - y = -4 ----------------------(I)

4x - 3y = -6 ---------------------(II)

Multiply equation (I) by (-3)

(I)*(-3) -36x + 3y = 12

(II) 4x - 3y = - 6 {Add and y will be eliminated}

- 32x = 6

x = 6/-32

x = -3/16

Plugin the value of x in equation (I)


12*(-3)/(16) -y=-4\\\\3*(-3)/(4)-y=-4\\\\(-9)/(4)-y = -4\\\\-y=-4+(9)/(4)\\\\-y=(-4*4)/(1*4)+(9)/(4)\\\\-y=(-16)/(4)+(9)/(4)\\\\-y=(-7)/(4)\\\\y=(7)/(4)\\\\y=1(3)/(4)

User KostyaEsmukov
by
4.8k points